Determination Factor Alumni and Student of Economic Faculty Lamongan Islamic University to Become Enterpreneur - Nanto Purnomo; Abid Muhtarom (Akuisisi: Jurnal Akuntansi, 2018)
ABSTRAK The current condition of the world in a work becomes more difficult while the people that need the job continues to increase. One way to solve the current conditions with make the employment not seeking job namely entrepreneur. According to the data from the BPS the level of entrepreneurship in Indonesia have increased in the 2013/2014 and still 1.67 percent and now based on data BPS already rose to 3.1 percent. This was allegedly caused by an improvement in the motivation from both internal factors and external factors. The problems in the search is how the influence of the risk tolerance factor, freedom in working, success themselves in pushing the entrepreneurs decision either partially or simultaneously and which the dominant factors.This research uses the validity Test, Test reliability, classical assumptions, double linier Regression, double correlation, Determination Test, F and t tests. The results of the analysis showed that the questionnaire used in the collection of data is valid and reliable and does not have the problem of classical assumptions. Y = 3,790 + 0,246 X1 + 0,242 X2 + 0,313 X3, R = 0,705. F count ( 29,585) > F table (2.71). From t test, obtained : t count x1y t (2,624); x2y (3,083): x3y (3,569) > t table (1,987). From the explanation is deduced the existence of a significant influence of both simultaneously  and partially  between independent variables against the Decision of the Entrepreneurs at the Faculty Of Economics University of Islam Lamongan. The results of this study are expected, can be made in consideration in motivating and developing learning about entrepreneurship at Islamic University of Lamongan Key Words : Motivation risk tolerance, freedom in working, success themselves & the decision entrepreneurs.